2023
DOI: 10.1002/chem.202203387
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Photocatalytic Carbon Dioxide Reduction by Tuning the Properties of Cocatalysts

Abstract: Suppressing the amount of carbon dioxide in the atmosphere is an essential measure toward addressing global warming. Specifically, the photocatalytic CO2 reduction reaction (CRR) is an effective strategy because it affords the conversion of CO2 into useful carbon feedstocks by using sunlight and water. However, the practical application of photocatalyst‐promoting CRR (CRR photocatalysts) requires significant improvement of their conversion efficiency. Accordingly, extensive research is being conducted toward i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 447 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Generally, relatively large‐sized Cu NPs are used for CRR electrocatalysts, but recent studies have reported that ultrafine ligand‐protected metal NCs with a particle size of ca. 1 nm can be used for various electrocatalysts [29] (including the CRR) [5a,b] and cocatalysts for photocatalysis [30] . A common feature of NCs is that many ligand‐protected metal NCs can be obtained as single crystals as well as metal complexes, [31] and their chemical compositions as well as geometric structures can be synthesized with atomically precise accuracy [32] .…”
Section: Electrochemical Co2 Reduction Reactionmentioning
confidence: 99%
“…Generally, relatively large‐sized Cu NPs are used for CRR electrocatalysts, but recent studies have reported that ultrafine ligand‐protected metal NCs with a particle size of ca. 1 nm can be used for various electrocatalysts [29] (including the CRR) [5a,b] and cocatalysts for photocatalysis [30] . A common feature of NCs is that many ligand‐protected metal NCs can be obtained as single crystals as well as metal complexes, [31] and their chemical compositions as well as geometric structures can be synthesized with atomically precise accuracy [32] .…”
Section: Electrochemical Co2 Reduction Reactionmentioning
confidence: 99%
“…Metal nanoclusters have attracted wide attention because of their atom-precise structures and quantum size effects, which provide an ideal platform for investigating the connection between simple metal complexes and bulk metal nanoparticles. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In addition, their potential applications in optics, [17][18][19][20] catalysis, [21][22][23][24][25] and biomedicine [26][27][28] encourage us to synthesize novel structured nanoclusters to exploit versatile properties. Among these, nanoclusters with valence electron structures similar to atomic electron structures are considered "superatomic nanoclusters".…”
Section: Introductionmentioning
confidence: 99%
“…To reduce atmospheric CO 2 , numerous efforts employing various innovative methods have been made, including the reduction of CO 2 through photochemical, 17-19 electrochemical [20][21][22][23] and biological approaches 24 into valuable compounds such as formic acid, formaldehyde, methanol and hydrocarbons; the co-reduction with nitrate to produce urea; 25 the incorporation of CO 2 into polymer main chains via copolymerization; [26][27][28] and composting with biomass. 29,30 These methods offer new avenues for xing CO 2 and producing materials composed of it.…”
Section: Introductionmentioning
confidence: 99%